Quantum-Classical Wigner-Liouville Equation - Kapral, R.; Sergi, A. (Український математичний журнал, 2005)
We consider a quantum system that is partitioned into a subsystem and a bath. Starting from the Wigner transform of the von Neumann equation for the quantum-mechanical density matrix of the entire system, the quantum-classical Wigner-Liouville equation is obtained in the limit where the masses M of the bath particles are large as compared with the masses m of the subsystem particles. The structure of this equation is discussed and it is shown how the abstract operator form of the quantum-classical Liouville equation is obtained by taking the inverse Wigner transform on the subsystem. Solutions in terms of classical trajectory segments and quantum transition or momentum jumps are described. Розглянуто квантову систему, розділену на підсистему та термостат. Після застосування перетворень Вігнера до рівняння фон Неймана для квантово-механічної матриці щільності системи одержано квантово-класичне рівняння Вігнера-Ліувілля у границі, де маси M частинок термостату великі у порівнянні з масами m частинок підсистеми. Обговорено структуру цього рівняння і показано, як можна отримати абстрактну операторну форму квантово-класичного рівняння Ліувілля за допомогою зворотного перетворення Вігнера на підсистемі. Розв'язки описано в термінах класичних сегментів траєкторії та квантового переходу або імпульсних стрибків.